Kerjasama Orang Tua dan Guru dalam Memotivasi Anak Menghafal Al-Qur’an di Rumah Tahfidz Nurul Qur’ani - Ajnaimah, Siti; Ibrahim, Duski; Oviyanti, Fitri (Jayapangus Press, 2023)
Parents and teachers have the responsibility to introduce and teach religious knowledge to children. In the process of memorizing the Koran, the role of parents and teachers in motivation is a very important dynamic aspect. With inner motivation, the memorization process will be maximized. Many children's lack of achievement is not due to their lack of ability, but because they lack motivation to learn. This research aims to analyze the strategies of teachers and parents in motivating children to memorize the Al-Qur'an. The research method used is qualitative with a case study approach. The results of this research show that 1) the teacher uses strategies by memorizing verses sequentially, deposits, Talaqqi and Muroja'ah methods. Apart from that, the teacher does not move on to another verse, before the verse is completely memorized, repeats the memorized memorization, muroja'ah when students deposit their memorization; 2) parents use strategies by listening to children's memorization, and Muraja'ah; and 3) there are several types of collaboration between parents and teachers, namely parenting; communication between parents and teachers either directly or indirectly; and volunteerism.